Aqua‐processable carbon quantum dot–assisted resilient polymer binder for advanced lithium‐sulfur batteries. (10th August 2021) - Kim, Soochan; Kim, Jungmin; Kim, Minhyeong; Cho, Misuk; Lee, Youngkwan
Summary: Lithium‐sulfur batteries (LSBs) with outstanding theoretical capacity and environmentally friendly properties are regarded as next‐generation energy storage devices. However, the shuttle effect of lithium polysulfide (LPS) limits the practical application of LSBs. Herein, we introduce an aqua‐processable carbon quantum dot (CQD)–assisted resilient waterborne polyurethane (WPU) network binder for sulfur cathodes. WPU is a well‐dispersed colloidal system with abundant polar groups that is suitable for regulating LPS shuttle effects. CQDs were prepared from WPU by hydrothermal treatment. The CQDs enabled facile electron/ion transport, enhanced the adsorption capability of LPS, and formed a robust network. Moreover, the chemical similarity between WPU and CQDs enabled the formation of a well‐dispersed system, thereby affording optimal electrochemical performance. The WPU‐CQD binder systems exhibited stable cycling performance at a high rate of 2C, with only 0.028% retention decay per cycle over 1000 cycles. Abstract : An aqueous‐processable multifunctional binder for high‐performance Li−S batteries was developed using a network of polyurethane and CQDs derived from polyurethane.